Profiling Farmer Innovations Around Legume Technologies - Lilongwe University of Agriculture and Natural Resources; Agriculture Extension Services; Michigan State University (International Food Policy Research Institute, 2017)
This study contains data based on investigations on technologies being used by farmers in Malawi as part of sustainable intensification. Project title: Africa Rising Malawi-Nutrition. Project abstract: The project focuses on profiling farmer innovations around legume technologies